2008
DOI: 10.2172/945380
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analyses of Advanced Fuel Cycles

Abstract: Alternative fuel cycles, 3) Impact of Time-of-implementation of alternative fuel cycles. 4) Use high burnup fuel (i.e. 70 GWth-d/tonne), 5) Reprocessing of LWR fuel, 6) Use Mixed Oxide (MOX) fuel, 7) Introduction of FRs in to the LWR fleet, 8) Inventories of Plutonium (Pu) and other actinides in and out of reactors, 9) Economic impact of alternative fuel cycles, and 10) Uncertainties of parameters and outcomes. Salient issues associated with these topics are addressed in the main body of this report and detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Prior authorization is a strategy used by many private and public health insurers to contain costs and improve the integrity of billing and treatment. 1 It is used across a wide array of services, including surgeries, hospital inpatient admissions, drugs, home health, and physical therapy. In the Medicare fee-for-service program, the Centers for Medicare & Medicaid Services (CMS) has focused prior authorization on a smaller set of services with documented high levels of improper payments and unnecessary use, which we refer to here as services vulnerable to improper use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior authorization is a strategy used by many private and public health insurers to contain costs and improve the integrity of billing and treatment. 1 It is used across a wide array of services, including surgeries, hospital inpatient admissions, drugs, home health, and physical therapy. In the Medicare fee-for-service program, the Centers for Medicare & Medicaid Services (CMS) has focused prior authorization on a smaller set of services with documented high levels of improper payments and unnecessary use, which we refer to here as services vulnerable to improper use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that prior authorization was associated with reduced spending for the targeted medication or service, though in some cases this association waned over time. [1][2][3][4][5][6][7][8][9] Findings related to the association of prior authorization with total cost of care are mixed, and there is limited evidence on changes in hospitalizations, emergency department visits, time to treatment, patient length of stay, or access to treatment. 1,3,7,10 By examining total cost of care and a series of patient outcomes and access to care measures, not just spending for the target service, this study is able to assess the potential for targeted prior authorization programs to improve efficiency in the Medicare program without a change in beneficiaries' health.…”
Section: Introductionmentioning
confidence: 99%